2024
DOI: 10.1027/0227-5910/a000896
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Emergencies and Suicide Attempts Before and During COVID-19 Lockdown in Spain

Abstract: Abstract. Background: The COVID-19 pandemic had a significant impact on the mental health of the population. The lockdown period in Spain – from March 14 to June 21, 2020 – was particularly stressful. This study aims to examine the differences in visits to the emergency department for psychiatric reasons before and during the lockdown period in a hospital in the province of Lleida (Catalonia, Spain), which has a catchment area of 431,183 inhabitants. We hope that this study can contribute to the understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…These findings add to the extant literature in that they address how variation in the severity of exposure to pandemic-related stressors across individuals and countries can impact suicide risk. Likewise, these results may shed light on previous findings of a decrease in suicide deaths 7,8 or suicide-related emergency room visits 9 in the early stage of the pandemic. Our findings point to an effect of time, such that chronicity of exposure to pandemic stressors appears to increase the severity of SCS symptoms.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…These findings add to the extant literature in that they address how variation in the severity of exposure to pandemic-related stressors across individuals and countries can impact suicide risk. Likewise, these results may shed light on previous findings of a decrease in suicide deaths 7,8 or suicide-related emergency room visits 9 in the early stage of the pandemic. Our findings point to an effect of time, such that chronicity of exposure to pandemic stressors appears to increase the severity of SCS symptoms.…”
Section: Discussionsupporting
confidence: 65%
“…Likewise, in a Spanish study of emergency room (ER) visits pre and post lockdown, there was a decrease in both the number of visits to the ER and in patients presenting with suicidal behavior in the initial 3 months of the pandemic. 9 The authors speculated, however, that suicide risk might change over time as the pandemic persisted. Likewise, a whole population-based study from Wales showed a decrease in suicide rates during the pandemic along with an increased rate of deaths of unknown cause.…”
Section: The Suicide Crisis Syndrome (Scs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The data for this study have been obtained through a longitudinal review of electronic health records (EHR) regarding all patients under 18 years of age who were assessed in the emergency room (ER) for acute psychiatric requests during the two COVID con nements in Spain ( rst state of emergency from March 15, 2020, to June 20, 2020; second state of emergency from October 25, 2020, to May 9, 2021 24 ). During this time, a state of alarm was decreed, schools were closed, and citizens were ordered to stay at home except for justi ed reasons, such as unavoidable work, purchase of food, or attendance at health centers for urgent reasons 25 . The rst contact with the psychiatric emergency department during the two COVID con nements was de ned as the index episode (i.e., the rst assessment in the psychiatric emergency room during one of the two states of emergency).…”
Section: Sample and Study Designmentioning
confidence: 99%
“…The need of additional beds compatible with mechanical ventilation (2) reduced bed capacity in mental health inpatient services (3). Di culties in accessing emergency departments (EDs) due to the high number of COVID-19 patients may have decreased the overall number of psychiatric visits (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%